2017
DOI: 10.3389/fpsyg.2017.00076
|View full text |Cite
|
Sign up to set email alerts
|

Want More? Learn Less: Motivation Affects Adolescents Learning from Negative Feedback

Abstract: The primary goal of the present study was to investigate how positive and negative feedback may differently facilitate learning throughout development. In addition, the role of motivation as a modulating factor was examined. Participants (children, adolescents, and adults) completed two forms of the guess and application task (GAT). Feedback from the Cool-GAT task has low motivational salience because there are no consequences, while feedback from the Hot-GAT task has high motivational salience as it pertains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The ability to learn from feedback in adolescence may also be enhanced, in part, by increasing levels of functional connectivity between the striatum and medial prefrontal cortex (Van Den Bos et al, 2012). Note, however, that learning from feedback becomes progressively more difficult for adolescents as the motivation for reward or task complexity increases (Davidow et al, 2018;Zhuang et al, 2017).…”
Section: Neurodevelopmental Shifts In Reward Sensitivity Enhance the Reinforcement Of Nssimentioning
confidence: 99%
“…The ability to learn from feedback in adolescence may also be enhanced, in part, by increasing levels of functional connectivity between the striatum and medial prefrontal cortex (Van Den Bos et al, 2012). Note, however, that learning from feedback becomes progressively more difficult for adolescents as the motivation for reward or task complexity increases (Davidow et al, 2018;Zhuang et al, 2017).…”
Section: Neurodevelopmental Shifts In Reward Sensitivity Enhance the Reinforcement Of Nssimentioning
confidence: 99%
“…is lower than 5, incremental indexes (CFI, IFI and TLI) are higher than .90 and mistake indexes (RMSEA and RMSR) are lower than .08 (Browne & Cudeck, 1993;Hu & Bentler, 1999). The maximum-likehood estimation method was used with bootstrapping procedure, since the result of Mardia multivariate coefficient was 25,35, what indicates lack of multivariate normality being beneath the reference value of 70 (Rodríguez & Ruiz, 2008). That is also the reason why, following to Finney and DiStefano (2006), the robust maximum-likehood estimation method (Byrne, 2001) was used.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Likewise, the way to show both the contents and the assessment results may stand for a big influence in the student's motivation. (Silveira, 2018;Zhuang, Feng, and Liao, 2017). It means, the student's motivation could be enhanced by little changes made by the teacher in the educative environment, as long as the special features were attended (Engelschalk et al, 2016;Orsini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hämmerer et al (2011) found that children were more sensitive to loss (negative feedback) than to gain (positive feedback). However, others studies found that children additionally show higher sensitivity to positive feedback ( Lange-Küttner et al, 2012 ; Hentschel et al, 2016 ; Zhuang et al, 2017 ). For instance, Lange-Küttner et al (2012) investigated the influence of feedback by a sequence learning task which involves deductive reasoning on a larger sample of 8- to 11-year-old children.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies ( Diamond, 2002 ; Sowell et al, 2004 ; Crone et al, 2006a , b ; Durston et al, 2006 ; Luciana and Collins, 2012 ; Ferdinand and Kray, 2014 ; Gennatas et al, 2017 ), which suggested that the biological structure and the psychological function of the frontal lobes differed markedly between the children and adults, we predicted that compared to adults, children might show a different pattern of ERP response to the informative value of feedback. Particularly, children might be less sensitive to the informative value of negative feedback, since they were more likely to be driven by positive feedback ( Somsen, 2007 ; van der Veen et al, 2008 ; Zhuang et al, 2017 ). In addition, based on the results of the two studies in our laboratory ( Li et al, 2011 ; Huang et al, 2013 ), we predicted that the processes of informative value of feedback for children might be observed at the left sites.…”
Section: Introductionmentioning
confidence: 99%